Ce-doped copper oxide-loaded Ru ammonia decomposition hydrogen production catalyst and preparation method thereof

By using Ce doped copper-supported Ru catalyst, the molar ratio of Cu and Ce was adjusted to 1: (10-10.2), and the Ru/CuCe10 catalyst was prepared, which solved the problem of insufficient catalytic performance and inactivation of existing catalysts at low temperatures, and achieved efficient ammonia decomposition under 500°C to produce hydrogen, which was suitable for industrial production.

CN118454690BActive Publication Date: 2025-04-11SICHUAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410652213.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-04-11
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

The existing ammonia decomposition hydrogen production catalysts have insufficient catalytic performance under low temperature conditions and have problems with catalyst deactivation, making it difficult to meet the needs of industrial production.

Method used

The Ru/CuCe10 catalyst was prepared by using a Ce-doped copper-supported Ru-based catalyst, by adjusting the molar ratio of Cu element to Ce element to 1: (10-10.2), and it was suitable for industrial mass production through a simple synthesis method.

Benefits of technology

Under 500°C, the Ru/CuCe10 catalyst showed excellent long-term activity stability, with an ammonia decomposition conversion rate of more than 80%, which was significantly better than previous research results, and could still maintain high activity under high temperature conditions, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118454690B_ABST
    Figure CN118454690B_ABST
Patent Text Reader

Abstract

The invention provides a Ce-doped copper oxide-loaded Ru ammonia decomposition hydrogen production catalyst and a preparation method thereof. The preparation method comprises firstly adding copper salt and cerium nitrate into a strong alkaline solution, mixing and configuring to obtain an intermediate mixed solution, and then sealing and heating the intermediate mixed solution, filtering to obtain a precipitate, and then successively roasting and grinding to obtain CuCe 10 The ruthenium element is loaded on the CuCe by impregnation method. 10 Ru / CuCe 10 Catalyst. The Ru / CuCe 10 The catalyst can be used at a mass space velocity (WHSV) of 30000ml / (g cat h) Environment, 10% NH 3 / Ar (50ml / min), showing surprisingly excellent long-term activity stability. At the same time, its relatively simple synthesis method is suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ammonia decomposition hydrogen production catalysts and relates to a Ce-doped copper oxide-loaded Ru ammonia decomposition hydrogen production catalyst and a preparation method thereof. Background Art

[0002] At present, more than 95% of H2 production in the world is obtained by steam reforming, gasification or oxidation of fossil fuels. In order to meet increasingly stringent carbon emission policies, the high cost of CO2 capture, storage and purification must be taken into account. The current methods of hydrogen production include fossil energy hydrogen production, water electrolysis hydrogen production, biohydrogen production, and industrial byproduct hydrogen production. However, fossil energy hydrogen production technology consumes a lot of energy and pollutes the environment. Water electrolysis hydrogen production is divided into four types: alkaline water electrolysis technology (ALK), proton exchange membrane water electrolysis technology (PEM), high temperature solid oxide water electrolysis technology (SOEC), and solid polymer anion exchange membrane water electrolysis technology (AEM). ALK uses a diaphragm to bring two limitations. One is that the gas is easy to permeate, and excessive permeation will cause an explosion risk. The other is that the current density is low, the volume of the electrolyzer is large, the heat capacity is large, and it is limited by the temperature response during cold start. The cathode catalyst of PEM is prone to decay in a strong acid electrolytic cell, and the transition metal dissolves and adheres to the membrane, reducing the mass transfer capacity of the membrane. At the same time, the anode oxygen evolution catalyst is also a difficulty. The main limitation of SOEC's promotion and use is its operating temperature of 1000°C. The problem faced by AEM is that the thermal and chemical stability of the anion exchange membrane is poor, and the anion conductivity is limited, which restricts the life and electrolytic performance of the AEM electrolytic cell. There are three main problems affecting the industrial development of biomass hydrogen production: first, the feedback produced by the accumulation of volatile acids in dark fermentation inhibits the production of hydrogen; second, the light energy conversion efficiency in microbial photolysis of water to produce hydrogen is low; third, in the light-dark coupled fermentation hydrogen production, the dark fermentation produces acid too quickly, which reduces the pH value, thereby inhibiting the growth of light-fermentation hydrogen-producing bacteria and reducing the overall hydrogen production efficiency. The technical difficulty of hydrogen production from industrial by-products lies mainly in the purification technology, among which CO is the most difficult impurity to handle in hydrogen.

[0003] Ammonia decomposition to produce hydrogen has the advantages of no CO x 、SO x 、NO x It does not emit CO2 and does not harm the ecological balance, which is unmatched by other carbon-containing raw materials for hydrogen production. Due to the high hydrogen content of ammonia (weight 17.8%, volume density 121kgH2m -3 , 10 bar) and is carbon-free, so it is often considered a viable option for chemical storage. Its energy density is 13.6 GJ m -3, which is between hydrogen and gasoline. Ammonia can be liquefied at 20°C and a low pressure of 8.6 bar, so it is relatively easy to transport and store. In terms of safety, the explosion limit of hydrogen is 4%-75%, and the explosion limit of ammonia in air is narrower, at 16%-25%, and a concentration as low as 5ppm can be easily detected by smell.

[0004] The decomposition reaction of NH3 is an endothermic reaction, 2NH3(g)→N2(g)+3H2(g)ΔH=46.22kJ / mol, and a high operating temperature is required to complete the ammonia decomposition reaction, thereby producing high-purity hydrogen. The high temperature required for the decomposition reaction leads to the necessity of energy supply. At the same time, there is a phenomenon of hydrogen poisoning in the ammonia decomposition catalyst that causes the catalyst to deactivate. There is a general consensus in the current research on ammonia catalysts, that is, Ru is the metal with the best activity in the ammonia decomposition reaction. Researchers have studied many metals loaded on Al2O3 particles, and they reported that the order of activity of ammonia decomposition catalysts is: Ru>Ni>Rh>Co>Ir>Fe>Pt>Cr>Pd>Cu.

[0005] In summary, there is an urgent need to solve the low-temperature catalytic performance and catalyst deactivation phenomenon of ammonia decomposition catalysts, improve the low-temperature catalytic performance and service life of catalysts, and at the same time prepare simple catalysts suitable for industrial production and application. Summary of the invention

[0006] In order to solve the above problems in the prior art, the present invention provides a Ce-doped copper oxide-loaded Ru ammonia decomposition hydrogen production catalyst and a preparation method thereof. The catalyst is specifically a Ru-loaded modified CuCe 10 Catalyst (Ru / CuCe 10 Catalyst), can be used at a mass space velocity (WHSV) of 30000ml / (g cat h) environment, under the condition of 500°C with the introduction of 10% NH3 / Ar (50 ml / min), it showed surprisingly excellent long-term activity stability. At the same time, its relatively simple synthesis method can be applied to industrial large-scale production.

[0007] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.

[0008] The present invention provides a method for preparing a Ce-doped copper oxide-loaded Ru ammonia decomposition hydrogen production catalyst, which mainly comprises the following steps:

[0009] (1) adding an appropriate amount of copper salt and 2.52-2.55 g of cerium nitrate to a strong alkaline solution having a hydroxide ion molar concentration of 5-6 mol / L, stirring until the cerium nitrate is fully dispersed to obtain an off-white intermediate mixed solution;

[0010] The copper salt is added in an amount such that the molar ratio of Cu element to Ce element is 1:(10-10.2);

[0011] (2) heating the mixed solution obtained in step (1) to 95-105° C. and maintaining the temperature for at least 24 hours, and filtering to obtain a precipitate after cooling;

[0012] (3) The precipitate obtained in step (2) is calcined and ground in sequence to prepare CuCe 10 Carrier powder;

[0013] (4) Weigh the CuCe obtained in step (3) 10 1g of carrier powder is added to 20-40ml of ultrapure water to prepare a carrier mixed solution, and an appropriate amount of ruthenium salt is added and stirred evenly to form a Ru-carrier dispersion;

[0014] Wherein, the amount of the ruthenium salt added is calculated in such a way that the ruthenium element loading is 1 to 3 wt%;

[0015] (5) Evaporate the Ru-support dispersion obtained in step (4) to remove water, thereby obtaining Ru / CuCe 10 catalyst.

[0016] In this article, the copper salt described in step (1) is selected from the copper salt raw material conventionally used in the copper ion solution. Those skilled in the art can make specific selections based on the conventional copper salts known in the prior art that can be added to the copper ion solution and in combination with actual needs, including but not limited to hydrated copper nitrate, anhydrous copper nitrate, and hydrated copper acetate. In order to simplify the experimental operation and facilitate the design of control experiments, the copper salt selected in the specific embodiment of the present invention is copper nitrate trihydrate (Cu(NO3)2·3H2O). Those skilled in the art should clearly realize that the copper salt described in step (1) is mainly to provide copper ions, and the selection of its specific anion root usually does not affect the technical effect achieved by the present invention.

[0017] Herein, the strong base in step (1) is a strong base commonly used in the chemical industry, such as sodium hydroxide and potassium hydroxide.

[0018] It should be noted that the stirring in step (1) until the cerium nitrate is fully dispersed to obtain an off-white intermediate mixed solution usually requires stirring for 30 to 35 minutes based on the addition amount calibrated in step (1) and laboratory conditions. Considering the chemical amplification effect, the specific stirring time can be based on the mixture turning into an off-white color.

[0019] It should be noted that the amount of copper salt added in step (1) is added in a molar ratio of Cu element to Ce element of 1: (10-10.2), which limits an extremely narrow range. This is because the present invention found in variable experiments that the ratio of Cu element to Ce element will greatly affect the long-term activity stability of the prepared catalyst, and the ratio is limited based on this experimental fact.

[0020] In this article, in step (3), the precipitate obtained in step (2) is successively calcined and ground. It is preferred that the precipitate be washed and dried before calcination. However, those skilled in the art should be aware that washing and drying the precipitate obtained by filtration is a conventional process in the chemical industry. Those skilled in the art can select appropriate washing and drying methods according to common knowledge or conventional processes.

[0021] In order to better illustrate the present invention and provide a technical solution for reference, the precipitate obtained in step (1) is successively roasted and ground in step (2), and the precipitate is washed and dried before roasting. The washing is performed by alternating deionized water and anhydrous ethanol for at least 3 times to better remove impurity ions in the precipitate; the drying is preferably performed by drying the washed precipitate at a temperature of 75 to 85° C. for at least 12 hours, and maintaining the drying process until roasting.

[0022] In this article, the precipitate obtained in step (2) is successively roasted and ground as described in step (3), wherein the roasting is to convert the metal components in the precipitate into oxides, specifically following the conventional roasting method / roasting parameters in the chemical process. Those skilled in the art can directly refer to the conventional method of roasting to prepare copper oxide and cerium dioxide for processing.

[0023] In one of the technical solutions, the precipitate obtained in step (2) is sequentially calcined and ground in step (3), wherein the specific process parameters of the calcination are: heating to 495-505°C at a heating rate of 2-2.1°C / min, maintaining at 495-505°C for 3-3.5h, and finally cooling to room temperature at a cooling rate of 2-2.1°C / min.

[0024] In this article, the precipitate obtained in step (2) is successively calcined and ground in step (3), wherein grinding is a conventional process for processing the calcined product into powder, following the conventional principles of chemical technology, and those skilled in the art can perform specific operations according to common knowledge.

[0025] In this article, the ruthenium salt described in step (4) is selected from the ruthenium salt raw material conventionally used in the ruthenium ion solution. Those skilled in the art can make specific selections based on the conventional ruthenium salts known in the prior art that can be added to the ruthenium ion solution and in combination with actual needs, including but not limited to any one of hydrated ruthenium trichloride, ruthenium trichloride, ruthenium acetate, and ruthenium oxide; in order to simplify the experimental operation and facilitate the design of control experiments, the ruthenium salt selected in the specific embodiment of the present invention is hydrated ruthenium trichloride (RuCl3·xH2O). Those skilled in the art should clearly realize that the ruthenium salt described in step (1) is mainly to provide ruthenium ions, and the specific selection of the ruthenium salt usually does not affect the technical effects achieved by the present invention.

[0026] In one of the technical solutions, when the ruthenium salt selected in step (4) is hydrated ruthenium trichloride, due to the hygroscopic nature of hydrated ruthenium trichloride, before adding, the weighed hydrated ruthenium trichloride should be mixed with a small amount of purified water to form a ruthenium ion solution to facilitate accurate addition.

[0027] In this article, the amount of ruthenium salt added in step (4) is calculated in such a way that the ruthenium element loading is 1 to 3 wt%. The loading is calculated based on the final prepared Ru / CuCe 10 The loading amount of ruthenium in the catalyst shall prevail.

[0028] In one of the technical solutions, step (5) is to evaporate the Ru-carrier dispersion obtained in step (4) to remove water, wherein the evaporation to remove water is specifically carried out by rotary evaporation.

[0029] In this article, the mixing, washing and drying all follow the conventional principles in chemical processes, and those skilled in the art can perform specific operations according to common knowledge.

[0030] The principle of the present invention is that the doping of Cu metal changes the structure of the CeO2 carrier, changes the electron transfer between the carrier and the active component, and then changes the interaction between the carrier and the active component. Cerium dioxide (CeO2), as a rare earth oxide, can produce abundant oxygen vacancies, which has a strong interaction with metals, and the Ce element can be in Ce 3+ and Ce 4 + Ce can hinder the sintering of Cu, form a strong interaction at the CuO-CeO2 junction, and enhance thermal stability.

[0031] The above invention principle is also recorded in the prior public paper (Li Shenghu. Exploration of Ce-Doped CuO Catalyst for Ammonia Decomposition to Produce Hydrogen [J]. Material Sciences, 2024, 14 (01): 51-60.), which describes in detail the specific characterization of the products, catalytic activity characterization and principle analysis of similar catalysts to the present invention, and focuses on the Ru / CuCe x The comparative analysis of the catalysts (x=0.5 / 1 / 5 / 12 / 50) will not be repeated here.

[0032] The inventive point of the present invention is that, based on the disclosure of the above research results, in order to provide sufficient experimental data for further industrial implementation, the inventor's research group further carried out a large number of exploratory experiments on the ratio variables of Cu and Ce elements. In this process, it was surprisingly found that when the molar ratio of Cu and Ce elements was 1: (10-10.2), the Ru / CuCe prepared by the inventor's research group was 1: (10-10.2). 10 The catalyst has excellent long-term activity stability at low temperatures. Its long-term activity stability at 500°C significantly exceeds that of Ru / CuCe, which has the highest ammonia decomposition activity at above 450°C reported in the paper. 12 At the same time, the ammonia decomposition activity test found that under 600℃ and normal pressure, Ru / CuCe 12 The catalyst ammonia decomposition conversion rate can reach 99%, compared with Ru / CuCe 10 The catalyst can reach 98% slightly inferior to Ru / CuCe 12 catalyst, but at 500℃ and atmospheric pressure, Ru / CuCe 10 The catalyst ammonia decomposition conversion rate is significantly better than Ru / CuCe 12 catalyst.

[0033] The present invention has the following beneficial effects:

[0034] 1. The present invention provides a Ce-doped copper oxide-loaded Ru ammonia decomposition hydrogen production catalyst and a preparation method thereof. The catalyst has a mass space velocity (WHSV) of 30000 ml / (g cat h) environment, when 10% NH3 / Ar (50ml / min) is introduced at 600°C, the ammonia decomposition conversion rate can reach more than 98%; and when 10% NH3 / Ar (50ml / min) is introduced at 500°C, the ammonia conversion rate can reach more than 80%, which is significantly better than the previous research results.

[0035] 2. Ru / CuCe provided by the present invention 10 The catalyst has excellent high-temperature stability and can still maintain its high activity after 50 hours of testing, indicating that the catalyst has good activity stability.

[0036] 3. Ru / CuCe provided by the present invention 10 The Ru loading in the catalyst is extremely low, which can effectively reduce costs, and has excellent industrial conversion prospects under relatively low catalytic temperature (500°C). At the same time, the process steps are simple and suitable for continuous production. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The Ru / CuCe prepared in Example 1 of the present invention 10 The dotted line graph of ammonia decomposition conversion rate under various temperature conditions of the catalyst (left figure) and the long-term activity stability change graph at 500°C (right figure).

[0038] Figure 2 The dotted line graph of ammonia decomposition conversion rate of the Ru / CuO catalyst prepared in comparative example 1 of the present invention under various temperature conditions (left figure) and the long-term activity stability change graph at 500°C (right figure) are shown.

[0039] Figure 3 The Ru / CuCe prepared in Comparative Example 2 of the present invention 0.5 The dotted line graph of ammonia decomposition conversion rate under various temperature conditions of the catalyst (left figure) and the long-term activity stability change graph at 500°C (right figure).

[0040] Figure 4 The dotted line graph of ammonia decomposition conversion rate of the Ru / CuCe5 catalyst prepared in comparative example 3 of the present invention under various temperature conditions (left figure) and the long-term activity stability change graph at 500°C (right figure) are shown.

[0041] Figure 5 The Ru / CuCe prepared in Comparative Example 4 of the present invention 12 The dotted line graph of ammonia decomposition conversion rate under various temperature conditions of the catalyst (left figure) and the long-term activity stability change graph at 500°C (right figure).

[0042] Figure 6 The Ru / CuCe prepared in Comparative Example 5 of the present invention 50 The dotted line graph of ammonia decomposition conversion rate under various temperature conditions of the catalyst (left figure) and the long-term activity stability change graph at 500°C (right figure). DETAILED DESCRIPTION

[0043] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed in the present invention.

[0044] The present invention provides a method for preparing a Ce-doped copper oxide-loaded Ru ammonia decomposition hydrogen production catalyst, which mainly comprises the following steps:

[0045] (1) adding an appropriate amount of copper salt and 2.52-2.55 g of cerium nitrate to a strong alkaline solution having a hydroxide ion molar concentration of 5-6 mol / L, stirring until the cerium nitrate is fully dispersed to obtain an off-white intermediate mixed solution;

[0046] The copper salt is added in an amount such that the molar ratio of Cu element to Ce element is 1:(10-10.2);

[0047] (2) heating the mixed solution obtained in step (1) to 95-105° C. and maintaining the temperature for at least 24 hours, and filtering to obtain a precipitate after cooling;

[0048] (3) The precipitate obtained in step (2) is calcined and ground in sequence to prepare CuCe 10 Carrier powder;

[0049] (4) Weigh the CuCe obtained in step (3) 10 1g of carrier powder is added to 20-40ml of ultrapure water to prepare a carrier mixed solution, and an appropriate amount of ruthenium salt is added and stirred evenly to form a Ru-carrier dispersion;

[0050] Wherein, the amount of the ruthenium salt added is calculated in such a way that the ruthenium element loading is 1 to 3 wt%;

[0051] (5) Evaporate the Ru-support dispersion obtained in step (4) to remove water, thereby obtaining Ru / CuCe 10 catalyst.

[0052] In this article, the copper salt described in step (1) is selected from the copper salt raw material conventionally used in the copper ion solution. Those skilled in the art can make specific selections based on the conventional copper salts known in the prior art that can be added to the copper ion solution and in combination with actual needs. In one embodiment, it includes but is not limited to hydrated copper nitrate, anhydrous copper nitrate, and hydrated copper acetate. In order to simplify the experimental operation and design the control experiment conveniently, the copper salt selected in the specific embodiment of the present invention is copper nitrate trihydrate (Cu(NO3)2·3H2O). Those skilled in the art should clearly realize that the copper salt described in step (1) is mainly to provide copper ions, and the selection of its specific anion root usually does not affect the technical effect achieved by the present invention.

[0053] Herein, the strong base in step (1) is a strong base commonly used in the chemical industry. In one embodiment, the strong base is sodium hydroxide or potassium hydroxide.

[0054] It should be noted that the stirring in step (1) until the cerium nitrate is fully dispersed to obtain an off-white intermediate mixed solution usually requires stirring for 30 to 35 minutes based on the addition amount calibrated in step (1) and laboratory conditions. Considering the chemical amplification effect, the specific stirring time can be based on the mixture turning into an off-white color.

[0055] It should be noted that the amount of copper salt added in step (1) is added in a molar ratio of Cu element to Ce element of 1: (10-10.2), which limits an extremely narrow range. This is because the present invention found in variable experiments that the ratio of Cu element to Ce element will greatly affect the long-term activity stability of the prepared catalyst, and the ratio is limited based on this experimental fact.

[0056] In this article, in step (3), the precipitate obtained in step (2) is successively calcined and ground. It is preferred that the precipitate be washed and dried before calcination. However, those skilled in the art should be aware that washing and drying the precipitate obtained by filtration is a conventional process in the chemical industry. Those skilled in the art can select appropriate washing and drying methods according to common knowledge or conventional processes.

[0057] In order to better illustrate the present invention and provide an implementation method for reference, the precipitate obtained in step (1) is successively roasted and ground in step (2), and the precipitate is washed and dried before roasting. The washing is performed by alternating deionized water and anhydrous ethanol for at least 3 times to better remove impurity ions in the precipitate; the drying is preferably performed by drying the washed precipitate at a temperature of 75 to 85° C. for at least 12 hours, and maintaining the drying process until roasting.

[0058] In this article, the precipitate obtained in step (2) is successively roasted and ground as described in step (3), wherein the roasting is to convert the metal components in the precipitate into oxides, specifically following the conventional roasting method / roasting parameters in the chemical process. Those skilled in the art can directly refer to the conventional method of roasting to prepare copper oxide and cerium dioxide for processing.

[0059] In one embodiment, the precipitate obtained in step (2) is sequentially calcined and ground in step (3), wherein the specific process parameters of the calcination are: heating to 495-505°C at a heating rate of 2-2.1°C / min, maintaining at 495-505°C for 3-3.5h, and finally cooling to room temperature at a cooling rate of 2-2.1°C / min.

[0060] In this article, the precipitate obtained in step (2) is successively calcined and ground in step (3), wherein grinding is a conventional process for processing the calcined product into powder, following the conventional principles of chemical technology, and those skilled in the art can perform specific operations according to common knowledge.

[0061] In this article, the ruthenium salt described in step (4) is selected from the ruthenium salt raw material conventionally used in the ruthenium ion solution. Those skilled in the art can make specific selections based on the conventional ruthenium salts known in the prior art that can be added to the ruthenium ion solution and in combination with actual needs. In one embodiment, it includes but is not limited to any one of hydrated ruthenium trichloride, ruthenium trichloride, ruthenium acetate, and ruthenium oxide. In order to simplify the experimental operation and facilitate the design of control experiments, the ruthenium salt selected in the specific embodiment of the present invention is hydrated ruthenium trichloride (RuCl3·xH2O). Those skilled in the art should clearly realize that the ruthenium salt described in step (1) is mainly to provide ruthenium ions, and the specific selection of the ruthenium salt will generally not affect the technical effects achieved by the present invention.

[0062] In one embodiment, when the ruthenium salt selected in step (4) is hydrated ruthenium trichloride, due to the deliquescent property of hydrated ruthenium trichloride, before adding, the weighed hydrated ruthenium trichloride is preferably mixed with a small amount of purified water to form a ruthenium ion solution to facilitate accurate addition.

[0063] In this article, the amount of ruthenium salt added in step (4) is calculated in such a way that the ruthenium element loading is 1 to 3 wt%. The loading is calculated based on the final prepared Ru / CuCe 10 The loading amount of ruthenium in the catalyst shall prevail.

[0064] In one embodiment, the amount of ruthenium salt added in step (4) is calculated so that the ruthenium element loading is 1 to 3 wt%, for example, 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, 2.0 wt%, 2.1 wt%, 2.2 wt%, 2.3 wt%, 2.4 wt%, 2.5 wt%, 2.6 wt%, 2.7 wt%, 2.8 wt%, 2.9 wt%, 3.0 wt% or any range or point value therebetween.

[0065] In one embodiment, step (5) comprises evaporating the Ru-carrier dispersion obtained in step (4) to remove water, wherein the evaporation to remove water is specifically carried out by rotary evaporation.

[0066] In this article, the mixing, washing and drying all follow the conventional principles in chemical processes, and those skilled in the art can perform specific operations according to common knowledge.

[0067] The principle of the present invention is that the doping of Cu metal changes the structure of the CeO2 carrier, changes the electron transfer between the carrier and the active component, and then changes the interaction between the carrier and the active component. Cerium dioxide (CeO2), as a rare earth oxide, can produce abundant oxygen vacancies, which has a strong interaction with metals, and the Ce element can be in Ce 3+ and Ce 4 + Ce can hinder the sintering of Cu, form a strong interaction at the CuO-CeO2 junction, and enhance thermal stability.

[0068] The above invention principle is also recorded in the prior public paper (Li Shenghu. Exploration of Ce-Doped CuO Catalyst for Ammonia Decomposition to Produce Hydrogen [J]. Material Sciences, 2024, 14 (01): 51-60.), which describes in detail the specific characterization of the products, catalytic activity characterization and principle analysis of similar catalysts to the present invention, and focuses on the Ru / CuCe x The comparative analysis of the catalysts (x=0.5 / 1 / 5 / 12 / 50) will not be repeated here.

[0069] The inventive point of the present invention is that, based on the disclosure of the above research results, in order to provide sufficient experimental data for further industrial implementation, the inventor's research group further carried out a large number of exploratory experiments on the ratio variables of Cu and Ce elements. In this process, it was surprisingly found that when the molar ratio of Cu and Ce elements was 1: (10-10.2), the Ru / CuCe prepared by the inventor's research group was 1: (10-10.2). 10 The catalyst has excellent long-term activity stability at low temperatures. Its long-term activity stability at 500°C significantly exceeds that of Ru / CuCe, which has the highest ammonia decomposition activity at above 450°C reported in the paper. 12 At the same time, the ammonia decomposition activity test found that under 600℃ and normal pressure, Ru / CuCe 12 The catalyst ammonia decomposition conversion rate can reach 99%, compared with Ru / CuCe 10 The catalyst can reach 98% slightly inferior to Ru / CuCe 12 catalyst, but at 500℃ and atmospheric pressure, Ru / CuCe 10 The catalyst ammonia decomposition conversion rate is significantly better than Ru / CuCe 12 catalyst.

[0070] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.

[0071] Example

[0072] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.

[0073] 1. Raw materials

[0074] name purity supplier <![CDATA[10%NH3 / Ar]]> ≥99.999% Chengdu Xuyuan Chemical Co., Ltd. Gas <![CDATA[20%H2 / Ar]]> ≥99.999% Chengdu Xuyuan Chemical Co., Ltd. Gas Ar ≥99.999% Chengdu Xuyuan Chemical Co., Ltd. Gas Cerium nitrate hexahydrate Analytical grade Chengdu Kelong Chemicals Co., Ltd. Copper Nitrate Trihydrate Analytical grade Chengdu Kelong Chemicals Co., Ltd. <![CDATA[RuCl3·xH2O]]> Analytical grade Shanghai MacLean Biochemical Technology Co., Ltd.

[0075] 2. Test Method

[0076] The catalyst was tested for ammonia decomposition activity in a fixed bed reactor at atmospheric pressure. Normally, 0.1 g of catalyst (sieved 20-40 mesh) was placed in a stainless steel reactor with an inner diameter of 8 mm. It was purged at 300 ° C under Ar atmosphere for 1 h, then heated to 350 ° C at a rate of 5 ° C / min, and the gas was changed to 20% H2 / Ar (30ml / min) for 1 h reduction; then the gas was changed to Ar, and the temperature was lowered to 300 ° C and purged for 30 min; finally, 10% NH3 / Ar (50ml / min) was introduced into the reactor, and the reactor was heated to the required temperature. The product was analyzed by gas chromatograph (GC9790Ⅱ), and the detection temperature range was 300-600 ° C, and an activity test point was taken every 50 ° C. Ammonia conversion rate calculation X NH3 :

[0077]

[0078] X NH3 is the conversion rate of ammonia,

[0079]

[0080]

[0081] 3. Preparation method

[0082] (1) adding an appropriate amount of copper nitrate trihydrate and an appropriate amount of cerium nitrate to 56 ml of a sodium hydroxide solution having a hydroxide ion molar concentration of 6 mol / L, and stirring until the cerium nitrate is fully dispersed to obtain an off-white intermediate mixed solution;

[0083] Wherein, the amount of copper nitrate trihydrate added is in a manner that the molar ratio of Cu element to Ce element is 1:10;

[0084] (2) heating the mixed solution obtained in step (1) to 100° C. in a sealed container and maintaining the temperature for 24 hours, and filtering to obtain a precipitate after cooling;

[0085] (3) The precipitate obtained in step (2) is washed, dried, roasted, and ground in sequence to prepare CuCe 10 Carrier powder;

[0086] The specific process parameters of the calcination are: heating to 500°C at a heating rate of 2°C / min, maintaining at 500°C for 3h, and finally cooling to room temperature at a cooling rate of 2°C / min;

[0087] (4) Weigh the CuCe obtained in step (3) 101 g of carrier powder is added to 30 ml of ultrapure water to prepare a carrier mixed solution, and an appropriate amount of hydrated ruthenium trichloride is added and stirred evenly to form a Ru-carrier dispersion;

[0088] Wherein, the amount of hydrated ruthenium trichloride added is calculated in such a way that the ruthenium element loading amount is 1wt%;

[0089] (5) The Ru-carrier dispersion obtained in step (4) is subjected to rotary evaporation to remove water, thereby obtaining Ru / CuCe 10 catalyst.

[0090] Example 1

[0091] In this example, Ru / CuCe was prepared according to the above-mentioned "3. Preparation method" 10 The catalyst comprises 0.140 g of copper nitrate trihydrate and 2.523 g of cerium nitrate in step (1) so as to make the molar ratio of Cu element to Ce element be 1:10.

[0092] The prepared Ru / CuCe 10 The catalyst was tested and calculated according to the above "2. Test Method" to obtain the ammonia conversion rate under various temperature conditions, such as Figure 1 As shown in the left figure, Ru / CuCe 10 The ammonia conversion rate of the catalyst increases with the increase of temperature. At 600°C, the ammonia conversion rate can reach more than 98%. Figure 1 As shown in the right figure, it can be seen that Ru / CuCe 10 In long-term tests, including activity stability tests of more than 50 hours, the catalyst still maintained a high activity, indicating that the catalyst has excellent catalytic activity.

[0093] Comparative Example 1

[0094] In this comparative example, CuO was used as a carrier, that is, in step (1) of the above “3. Preparation method”, only 0.117 g of copper nitrate trihydrate was added, and no cerium nitrate was added. The remaining steps were consistent with “3. Preparation method” to prepare a Ru / CuO catalyst.

[0095] The prepared Ru / CuO catalyst was tested and calculated according to the above "2. Test Method" to obtain the ammonia conversion rate under various temperature conditions, such as Figure 2 As shown in the left figure, the ammonia conversion rate of the Ru / CuO catalyst increases with the increase of temperature, but the ammonia conversion rate only reaches more than 90% at a temperature of 600°C. Figure 2 The middle right picture is a long-term activity test of the catalyst, and the results show that its catalytic activity shows a downward trend with increasing reaction time.

[0096] The results show that the catalyst obtained in Comparative Example 1 has low activity when not doped with Ce, and is almost inactive at temperatures below 450°C. A certain proportion of ammonia can be converted at temperatures above 450°C, and the ammonia conversion rate is close to 90% only at 600°C. However, its catalytic activity and stability are significantly inferior to those of Example 1, and the activity decreases with increasing reaction time.

[0097] Comparative Example 2

[0098] In this comparative example, Ru / CuCe was prepared according to the above-mentioned "3. Preparation method" 0.5 The catalyst is different in that the molar ratio of Cu element to Ce element is 1:0.5, the copper nitrate trihydrate in step (1) is 2.808 g, the cerium nitrate is 2.523 g, and the remaining steps are consistent with "3. Preparation method".

[0099] The prepared Ru / CuCe 0.5 The catalyst was tested and calculated according to the above "2. Test Method" to obtain the ammonia conversion rate under various temperature conditions, such as Figure 3 As shown in the left figure, Ru / CuCe 0.5 The ammonia conversion rate of the catalyst increases with the increase of temperature, but only at 600℃, the ammonia conversion rate is close to 90%; in the long-term activity test at 500℃, the ammonia conversion rate is low and shows a downward trend. The results are as follows Figure 3 As shown in the picture on the right.

[0100] The results show that the catalyst obtained in Comparative Example 2 has a low activity in the reaction temperature range when the molar ratio of Ce to Cu is 0.5, and its catalytic activity is significantly inferior to that of Example 1; and its catalytic activity stability test at 500°C for a long time is lower than that of Ru / CuCe 10 The activity of the catalyst decreases with time.

[0101] Comparative Example 3

[0102] In this comparative example, Ru / CuCe5 catalyst was prepared according to the above-mentioned "3. Preparation method", except that the molar ratio of Cu element to Ce element was 1:5, the copper nitrate trihydrate in step (1) was 0.281 g, and the cerium nitrate was 2.523 g, and the remaining steps were consistent with "3. Preparation method".

[0103] The prepared Ru / CuCe5 catalyst was tested and calculated according to the above "2. Test method" to obtain the ammonia conversion rate under various temperature conditions, such as Figure 4As shown in the left figure, the ammonia conversion rate of the Ru / CuCe5 catalyst increases with the increase of temperature. At 600°C, its ammonia conversion rate can reach more than 90%. However, in the long-term activity test at 500°C, the ammonia conversion rate is low and shows a downward trend. The results are as follows Figure 3 As shown in the picture on the right.

[0104] The results show that when the molar ratio of Ce to Cu in comparative example 3 is 5, its activity is relatively low in the reaction temperature range. Its catalytic activity is divided into two stages. When the temperature is below 450°C, its activity is slightly higher than that of Ru / CuCe in example 1. 10 The activity of the catalyst is significantly lower than that of the catalyst in Example 1 when the temperature is higher than 450°C. In the long-term activity stability test at 500°C, the activity of the catalyst is lower than that of the catalyst in Example 1. 10 The activity of the catalyst decreases with time.

[0105] Comparative Example 4

[0106] In this comparative example, Ru / CuCe was prepared according to the above-mentioned "3. Preparation method" 12 The catalyst is different in that the molar ratio of Cu element to Ce element is 1:12, the copper nitrate trihydrate in step (1) is 0.117 g, the cerium nitrate is 2.523 g, and the remaining steps are consistent with "3. Preparation method".

[0107] The prepared Ru / CuCe 12 The catalyst was tested and calculated according to the above "2. Test Method" to obtain the ammonia conversion rate under various temperature conditions, such as Figure 5 As shown in the left figure, Ru / CuCe 12 The ammonia conversion rate of the catalyst increases with the increase of temperature. At 600℃, the ammonia conversion rate can reach 99%. At the same time, in the long-term activity test at 500℃, the catalyst still maintains a high activity, indicating that the catalyst has excellent catalytic activity. The results are as follows: Figure 5 As shown in the picture on the right.

[0108] The results show that the catalyst obtained in Comparative Example 4 has a low activity in the reaction temperature range when the molar ratio of Ce to Cu is 12. When the temperature is below 400°C, its activity is similar to that of the Ru / CuCe catalyst in Example 1. 10 The activity of the catalysts is comparable, but when the temperature is higher than 450°C, its activity is significantly inferior to that of the catalyst in Example 1. It is further shown in the long-term activity stability test at 500°C that it is significantly lower than that of Ru / CuCe 10 catalyst; however, when the temperature condition is 600°C, its activity is slightly stronger than that of the catalyst in Example 1.

[0109] Comparative Example 5

[0110] In this comparative example, Ru / CuCe was prepared according to the above-mentioned "3. Preparation method" 50 The catalyst is different in that the molar ratio of Cu element to Ce element is 1:50, the copper nitrate trihydrate in step (1) is 0.028 g, the cerium nitrate is 2.523 g, and the remaining steps are consistent with "3. Preparation method".

[0111] The prepared Ru / CuCe5 catalyst was tested and calculated according to the above "2. Test method" to obtain the ammonia conversion rate under various temperature conditions, such as Figure 6 As shown in the left figure, Ru / CuCe 50 The ammonia conversion rate of the catalyst increases with the increase of temperature. At 600℃, the ammonia conversion rate can reach more than 80%. However, in the long-term activity test at 500℃, the ammonia conversion rate is low and shows a downward trend. The results are as follows: Figure 6 As shown in the picture on the right.

[0112] The results show that when the molar ratio of Ce to Cu in Comparative Example 5 is 50, the activity of the catalyst obtained in Comparative Example 5 is relatively low in the reaction temperature range. Its catalytic activity is divided into two stages. When the temperature is below 450°C, its activity is slightly higher than that of the Ru / CuCe catalyst in Example 1. 10 The activity of the catalyst is significantly lower than that of the catalyst in Example 1 when the temperature is higher than 450°C. In the long-term activity stability test at 500°C, the activity of the catalyst is lower than that of the catalyst in Example 1. 10 The activity of the catalyst decreases with time.

[0113] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a Ce-doped copper oxide-loaded Ru ammonia decomposition hydrogen production catalyst, characterized in that The main steps include: (1) Add an appropriate amount of copper salt and 2.52-2.55 g of cerium nitrate to a strong alkaline solution with a hydroxide ion molar concentration of 5-6 mol / L, and stir until the cerium nitrate is fully dispersed to obtain an off-white intermediate mixed solution; Wherein, the copper salt is added in an amount such that the molar ratio of Cu element to Ce element is 1:(10-10.2); (2) The mixed solution obtained in step (1) is sealed and heated to 95-105° C. and maintained at this temperature for at least 24 hours, and after cooling, filtered to obtain a precipitate; (3) The precipitate obtained in step (2) is calcined and ground in sequence to prepare CuCe 10 Carrier powder; (4) Weigh the CuCe obtained in step (3) 10 1g of carrier powder is added to 20-40ml ultrapure water to prepare a carrier mixed solution, and an appropriate amount of ruthenium salt is added and stirred evenly to form a Ru-carrier dispersion; Wherein, the amount of the ruthenium salt added is calculated in such a way that the ruthenium element loading is 1-1.5wt%; (5) Evaporate the Ru-support dispersion obtained in step (4) to remove water, thereby obtaining Ru / CuCe 10 catalyst.

2. The preparation method according to claim 1, characterized in that: The copper salt in step (1) includes any one of hydrated copper nitrate, anhydrous copper nitrate and hydrated copper acetate.

3. The preparation method according to claim 1, characterized in that: In step (3), the precipitate obtained in step (2) is sequentially roasted and ground, and the precipitate is washed and dried before roasting, wherein the washing is performed by alternating deionized water and anhydrous ethanol for at least 3 times; and the drying is performed by drying the washed precipitate at a temperature of 75-85°C for at least 12 hours, and maintaining the drying process until roasting.

4. The preparation method according to claim 1, characterized in that: In step (3), the precipitate obtained in step (2) is sequentially calcined and ground, wherein the specific process parameters of the calcination are: heating to 495-505°C at a heating rate of 2-2.1°C / min, maintaining at 495-505°C for 3-3.5h, and finally cooling to room temperature at a cooling rate of 2-2.1°C / min.

5. The preparation method according to claim 1, characterized in that: The ruthenium salt in step (4) includes any one of hydrated ruthenium trichloride, ruthenium trichloride, ruthenium acetate, and ruthenium oxide.

6. A Ru / CuCe prepared by the method for preparing a catalyst for hydrogen production from ammonia decomposition by Ce-doped copper oxide loaded with Ru according to claim 1 10 catalyst.

7. Ru / CuCe as claimed in claim 6 10 Application of catalysts in the field of ammonia decomposition to produce hydrogen.

8. The use according to claim 7, characterized in that: The catalytic reaction of ammonia decomposition to produce hydrogen is carried out at a temperature of at least 500°C.

Citation Information

Patent Citations

  • Ru-based catalyst for hydrogen production through ammonia decomposition and preparation method of Ru-based catalyst

    CN116139859A

  • Catalyst for ammonia decomposition, method for producing same, and method for producing hydrogen using same

    CN117015438A